Review of National and Regional Research and Innovation Strategies for Smart Specialization in Poland - Piatkowski, Marcin; Szuba, Tomasz; Wolszczak, Grzegorz (World Bank, Warsaw, 2014)
The report provides a brief summary of the existing Third Research and Innovation Strategy (RSI3s) and specifies the complementary activities that need to be undertaken on each level to fulfill the ex-ante conditionality as stipulated in the most recent draft general regulation of the European Commission, and to ensure strategic coherence across all documents. The report also assesses whether the draft RIS3s will contribute to the socio-economic transformation of the country. In the review, the report focuses on several important aspects, including: (i) formal fulfillment of ex ante conditionalties; (ii) coherence of key strategic documents within Poland s innovation framework; (iii) the overall quality of the framework; and (iii) smart specializations. As part of the assignment, the Bank and the Ministry of Regional Development organized a special workshop for all sixteen regions to present the report s initial findings, discuss conclusions and recommendations and follow up with regions and voivodships (regions) on specific areas of interest.